Dosimetric comparison of MR-guided adaptive IMRT versus 3DOF-VMAT for prostate stereotactic radiotherapy. (March 2022) - Kong, Vickie C.; Dang, Jennifer; Li, Winnie; Navarro, Inmaculada; Padayachee, Jerusha; Malkov, Victor; Winter, Jeff; Raman, Srinivas; Berlin, Alejandro; Catton, Charles; Warde, Padraig; Chung, Peter
Highlights: Prostate SBRT are treated using MR-guided adaptive IMRT (A-IMRT) and VMAT based on translation correction (3DOF-VMAT) at our institution. Comparison of reference and delivered dose between adaptive-IMRT and 3DOF-VMAT to assess the effect of interfractional motion. Despite large interfractional changes, prostate received clinically acceptable dose with a margin of 5 mm through either A-IMRT or 3DOF-VMAT. A-IMRT was more superior than 3DOF-VMAT in sparing the rectum in the high dose region; no difference between the two systems was observed for bladder. Abstract: Introduction: To compare the dosimetry of prostate stereotactic radiotherapy (SBRT) delivered by adaptive intensity modulated radiotherapy (A-IMRT) and 3 degree of freedom volumetric modulated arc therapy (3DOF-VMAT). Methods & Materials: Twenty-five prostate patients treated with High Dose Rate (HDR) brachytherapy followed by SBRT were included (fifteen with hydrogel spacer in place for treatment). Interfraction changes in the volume of prostate, rectum and bladder were measured. Fractional dose to these structures was estimated for A-IMRT and 3DOF-VMAT for comparison against the corresponding reference dose and between each other. Results: Clinically acceptable dose was delivered to prostate in all 125 fractions through A-IMRT and 3DOF-VMAT. A-IMRT was better than 3DOF-VMAT in reducing dose to 1 cm 3 of rectum. Conversely, 3DOF-VMAT was superior in sparing 50% and 20% of rectum. When comparing the reference and delivered dose, there was no significant difference for Bladder D5cm 3 for either technique. However, rectum in the high dose region benefited more from A-IMRT by being irradiated to a lower than reference dose in more fractions than 3DOF-VMAT. Hydrogel spacer reduced the rectal dose and was associated with a smaller deviation from reference dose for rectum D50% for A-IMRT. Conclusions: Despite the presence of large interfraction organ volumes changes, clinically acceptable dose was delivered to the prostate by both systems. A-IMRT facilitated a greater rectal sparing from the high dose region than 3DOF-VMAT. Further reduction in rectal dose could be achieved by hydrogel spacer to displace the rectum, or by adaptation delivered by VMAT.